ANALISIS STRATEGI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH AL HUDA CABANG KALIWIRO DALAM MENEKAN NON PERFORMING FINANCING (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to analyze the factors contributing to the high level of Non-Performing Financing (NPF) at KSPPS Al Huda Kaliwiro Branch, determine the institution's strategic position through SWOT analysis, and formulate strategies to maintain the NPF level below the healthy threshold (
Keywords: Non-Performing Financing (NPF); KSPPS Al Huda; SWOT Analysis